1994
DOI: 10.1017/s002221510012688x
|View full text |Cite
|
Sign up to set email alerts
|

Non-Explosive blast injury of the ear

Abstract: Non-explosive blast injury of the ear refers to the otological trauma caused by a blow to the ear that seals the external auditory meatus. It results in a sudden increase of air pressure within the ear canal that strikes the tympanic membrane. The present study portrays the various aspects of middle and inner ear damage in 91 patients resulting from an assault we entitled a ’non-explosive blast injury' to the ear. Sixty cases were caused by a slap or a fist, 13 patients suffered sport accidents, mostly in ball… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
29
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 10 publications
12
29
0
1
Order By: Relevance
“…1 Traumatic TM perforations are seen in all age groups. In our study, middle age group (20-40 years) has the highest incidence similar to studies undertaken by Gacek and Gacek and Berger et al 6,7 The incidence of traumatic perforation was found to be more in males (64%) compared to females (36%) which was similar to studies reported by Gacek and Gacek and da Lilly-Tariah and Somefun. 6,8 The high prevalence can be explained by the fact that most cases were road traffic accidents involving two wheelers and majority of the drivers were males.…”
Section: Discussionsupporting
confidence: 91%
“…1 Traumatic TM perforations are seen in all age groups. In our study, middle age group (20-40 years) has the highest incidence similar to studies undertaken by Gacek and Gacek and Berger et al 6,7 The incidence of traumatic perforation was found to be more in males (64%) compared to females (36%) which was similar to studies reported by Gacek and Gacek and da Lilly-Tariah and Somefun. 6,8 The high prevalence can be explained by the fact that most cases were road traffic accidents involving two wheelers and majority of the drivers were males.…”
Section: Discussionsupporting
confidence: 91%
“…This is mainly due to prevalence of domestic violence and child abuse in our society. Lindeman et al 14 and Berger et al 15 also reported higher incidence of traumatic TM perforation amongst young females as in our series while Camintz et al 16 reported high prevalence in males. The most common side affected was the left side (51.7%) in our series while right ear was injured in 32.8% of cases and bilateral involvement was seen in 15.5 % of cases.…”
Section: Discussionsupporting
confidence: 71%
“…Al-Obiedi SH, Lindeman, Berger also had similar prelidiction for the left ear. 5 , 14,15 Most of the patients in our series(55.2%) had small perforation with involvement of around 20% of the TM size. Large perforation involving 80% of TM size was seen only in 1.7% cases.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations